The correct answer is <em><u>-0.6</u></em> which in fraction form is <u><em>-3/5</em></u>
Your answer is <u><em>C. -3/5</em></u>
So the expression is:
![4 a^{2} + 2a + 4 a^{2} - 5](https://tex.z-dn.net/?f=4%20a%5E%7B2%7D%20%2B%202a%20%2B%204%20a%5E%7B2%7D%20-%205)
You can combine like terms, which are terms that contain the same variables raised to the same power. That means you can combine the two
![4 a^{2}](https://tex.z-dn.net/?f=4%20a%5E%7B2%7D)
.
![4 a^{2} + 4 a^{2} = 8 a^{2}](https://tex.z-dn.net/?f=4%20a%5E%7B2%7D%20%2B%204%20a%5E%7B2%7D%20%3D%208%20a%5E%7B2%7D)
The other terms can't be combined.
Your final answer should be
![8 a^{2} +2a-5](https://tex.z-dn.net/?f=8%20a%5E%7B2%7D%20%2B2a-5)
.
Answer:
The error she made was that she was adding x and 2.75. She should subtract 2.75 from x.
Another mistake that she made was that she sold each for $7 assuming that she would make a profit of 78, but she should see each necklace for $12.5 so that she could make a profit of $78.
Step-by-step explanation:
The error she made was that she was adding x and 2.75.
She should write the equation as 8 (x - 2.75) = 78; as she spends $2.75 to make a necklace.
By using the correct equation: 8 (x - 2.75) = 78
=> 8x - 22 = 78
=> 8x = 78 + 22
=> 8x = 100
=> x = 100/8
=> x = 12.5
Another mistake that she made was that she sold each for $7 assuming that she would make a profit of 78, but she should see each necklace for $12.5 so that she could make a profit of $78.
Hope this helps you.